(untitled) (Colombia Medica, 2019)
Case Description:We report the case of a one-year-old girl who was diagnosed with Wiedemann-Steiner Syndrome based on the identification of a novel de novo frameshift mutation in the KMT2A gene by whole exome sequencing and supported by her clinical features. Clinical Findings:KMT2A mutations cause Wiedemann-Steiner Syndrome, a very rare genetic disorder characterized by congenital hypertrichosis, short stature, intellectual disability, and distinct facial features. Treatment and Outcome:Whole exome sequencing identified a novel frameshift variant: c. 4177dupA (p.Ile1393Asnfs * 14) in KMT2A; this change generates an alteration of the specific binding to non-methylated CpG motifs of the DNA to the protein. The genotype and phenotype of the patient were compared with those of earlier reported patients in the literature. Clinical Relevance:In diseases with low frequency, it is necessary to establish a genotype-phenotype correlation that allows the establishment of therapeutic and follow-up goals. The phenotype comparation with other reported cases did not show differences attributable to sex or age among patients with Wiedemann-Steiner Syndrome. Whole exome sequencing allows identifying causality in conditions with high clinical and genetic heterogeneity like hypertrichosis.